2012
DOI: 10.1063/1.4746082
|View full text |Cite
|
Sign up to set email alerts
|

Accessing intermediate ferroelectric switching regimes with time-resolved transmission electron microscopy

Abstract: Piezoresponse force microscopic study of ferroelectric (1−x)Pb(Sc1/2Nb1/2)O3−xPbTiO3 and Pb(Sc1/2Nb1/2)O3 single crystals J. Appl. Phys. 112, 052009 (2012) Piezoresponse force microscopy studies on the domain structures and local switching behavior of Pb(In1/2Nb1/2)O3-Pb(Mg1/3Nb2/3)O3-PbTiO3 single crystals J. Appl. Phys. 112, 052006 (2012) Antiferroelectric-like properties and enhanced polarization of Cu-doped K0.5Na0.5NbO3 piezoelectric ceramics Appl. Phys. Lett. 101, 082901 (2012) BiFeO 3 (BFO) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…The work presented herein provides insight into the switching behavior of devices containing significant defect densities and directly shows the interactions between dislocations and domain walls, revealing a preference for domain nucleation to locally follow the NLS model over the KAI model, while the global behavior follows the KAI model. 17 The results prove that the direct impact of strain and defects is a crucial factor for determining the appropriate switching mechanism for ferroelectric domains in nanoscale device architectures.…”
Section: * S Supporting Informationmentioning
confidence: 86%
See 1 more Smart Citation
“…The work presented herein provides insight into the switching behavior of devices containing significant defect densities and directly shows the interactions between dislocations and domain walls, revealing a preference for domain nucleation to locally follow the NLS model over the KAI model, while the global behavior follows the KAI model. 17 The results prove that the direct impact of strain and defects is a crucial factor for determining the appropriate switching mechanism for ferroelectric domains in nanoscale device architectures.…”
Section: * S Supporting Informationmentioning
confidence: 86%
“…10−16 Both theoretical and experimental studies have shown that strain fields around threading dislocations result in ∼1 nm "dead" areas (near-zero polarization), which pin domain walls. 10,16,17 Variations in Burger's vectors of misfit or threading dislocations have also been shown to alter local domain morphology and nucleation behavior. 12 While the KAI model is typically used to describe domain switching in bulk and microscale ferroelectrics, the NLS model has been found to better fit thin-film devices and nanoscale capacitors.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…In comparison with general measurement techniques, in situ TEM can be used to directly observe atomicscale domain interactions in real time during switching through the thickness of the film, enabling switching dynamics to be correlated with local defect microstructures in real time 13,18,19 . Employing spherical aberration-corrected TEM with sub-angstrom resolution 20,21 , we are able to directly map the local polarization at the atomic scale [9][10] .…”
mentioning
confidence: 99%
“…Multiferroic materials exhibit the simultaneous existence of at least two of the ferroelectric, ferromagnetic, and ferroelastic coupled order parameters within a single phase in a certain range of temperatures [1,2]. They have recently attracted much attention due to the promising multifunctional device applications in information storage, sensor, spintronics, multi-states memory, etc.…”
Section: Introductionmentioning
confidence: 99%